Tubular Graphene Nano-Scroll Coated Silicon for High Rate Performance Lithium-Ion Battery - Shi, Minyuan; Nie, Ping; Fan, Zengjie; Fu, Ruirui; Fang, Shan; Dou, Hui; Zhang, Xiaogang (Frontiers in Energy Research, 2020)
Owing to the high specific capacity and abundant reserve, silicon has been considered as a promising anode material for next lithium storage. However, its cycle life is seriously hindered by the huge volume variation and low conductivity. Therefore, it is crucial to effectively and easily prepare silicon anode with excellent performance. Herein, we introduce a simple method to prepare graphene nano-scroll coated silicon nanoparticles (Si@rGONSs) on a large scale. With the open one-dimensional (1D) structure and high conductivity of graphene, the obtained Si@rGONSs-2 electrode delivers a superior rate capacity of 866 mAh g−1 at 5 A g−1 and a capacity retention of 89.4 % after 300 cycles. Furthermore, the Si@rGONSs// Li[Ni1/3Co1/3Mn1/3]O2 (NCM 111) full cell was successfully demonstrated, which achieves a stable capacity of 128.5 mAh g−1 at 0.5 C (1C=185 mAh g−1) and a high energy density of 406 Wh kg−1.